Expression of thymidylate synthase predicts clinical outcomes of S-1-based chemotherapy in squamous cell lung cancer - Honma, Yuichiro (Oncol Lett, 2017)
Non-small cell lung cancer (NSCLC) patients with squamous cell carcinoma (SCC) histology have limited chemotherapeutic options. Treatment with S-1 combined with carboplatin (CBDCA) has been shown to provide a significant survival benefit in SCC patients compared with treatment with combined CBDCA and paclitaxel. The aim of the present study was to investigate the association between the expression of molecular markers related to the pharmacological action of S-1, including thymidylate synthase (TS), orotate phosphoribosyltransferase (OPRT) and dihydropyrimidine dehydrogenase (DPD), and the clinical efficacy of S-1-based chemotherapy in SCC patients. The immunohistochemical expression of TS, OPRT and DPD were retrospectively analyzed in tumor biopsy and resection specimens from patients with advanced SCC (n=32). Immunohistochemical H-scores were calculated and their association with S-1/CBDCA response was evaluated. Median progression-free survival time was significantly longer in patients with low TS H-scores than in those with high TS H-scores (162.5 vs. 97 days; P=0.004); by contrast, overall survival time was not observed to differ significantly between these groups (P=0.185). In the multivariate analysis, low TS expression was a significant positive factor for progression-free survival rate (hazard ratio, 0.40; P=0.021). A low TS H-score was also associated with an increased response to S-1-based chemotherapy compared with a high TS H-score (P=0.002). This indicates that SCC patients with low TS expression can benefit significantly from S-1-based chemotherapy, and that H-score measurement of intratumoral TS expression may represent a useful predictive biomarker for response to S-1-based chemotherapy by patients with SCC-type NSCLC.